PENGEMBANGAN DAYA TARIK WISATA LEMBU PUTIH DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DI DESA WISATA TARO, TEGALLALANG, GIANYAR - Ni Komang Sixma Dewi; Wirawan, Putu Eka; Nyoman Agus Trimandala (UHN IGB Sugriwa Denpasar, 2024)
The development of tourist attractions is closely related to community participation. Local communities as tourism actors and also resource owners, should be involved in developing tourist attractions because community participation can help build various facilities needed for tourist attractions. The aim of this research is to determine the role of the community in developing the Lembu Putih tourist attraction. The method used is descriptive qualitative with data collection through observation, interviews and documentation. This research involved six sources, and data analysis techniques included data reduction, data presentation, and drawing conclusions. The research results explain the potential of the Lembu Putih tourist attraction and the participation of local communities in tourism development starting from planning, implementation, to evaluation and taking advantage of the tourist attraction. In developing the Lembu Putih tourist attraction there are several inhibiting factors faced by the manager, but behind these obstacles the manager has a future program to develop the Lembu Putih tourist attraction, such as arranging the tourist area, adding tourism support facilities.